A critical exposition of Bergson's process philosophy - Godwin Okon Asuquo; Iniobong D. Umotong; Otto Dennis (International Journal of Humanities and Innovation (IJHI), 2022)
This paper is a critical and expository study of the basic ideas in the process thought of Henri Bergson. Process philosophy is one of the oldest traditions in metaphysics, traceable to the doctrine of Heraclitus, an ancient Greek thinker. It is opposed to the idea of the Milesian thinkers like Thales and Anaximenes, who believed that reality consists of an unchanging substance that persists. Overtime, the view that reality is a novelty and, as such creative became a discourse of interest, either implicitly or explicitly, for many philosophers in the different epochs of western philosophy. As a result, different ideas emerged in an attempt to explain processes. However, these ideas have been discovered to point toward two directions – mechanism and finalism. As against this stance which pointed toward an end to the creative and novel posture of reality, Henri Bergson came up with his philosophy of multiple virtualities. However, how successful was his project? In this paper, therefore, we critically assess some strengths and weaknesses of the basic ideas in his thought process. However, though we have noted some inherent problems in his thought, Bergson’s idea of reality as multiple virtualities gives room to reality as continually processual, overcoming the mechanistic or finalistic you of other thinkers.